Effect Of Distributive Justice And Procedural Justice On Work Engagement - Muhamad Yusuf Firdaus; Evi Susanti; Tantri Yanuar Rahmat Syah (Journal of Multidisciplinary Academic, 2019)
The purpose of this paper aimed to explore whether perceptions of distributive and procedural justice are related to work engagement and possible relationship assessment between these two dimensions of justice. Here, we have 120 firefighters correspondent from the North Jakarta Fire Department. We analyse the observation data, using WarpPLS 6.0 software. The results showed that distributive justice and procedural justice were interrelated with one another. Furthermore, the procedural justice takes precedence over distributive justice in determining work engagement, followed by distributive justice. By highlighting the inter-relationships between the two dimensions of Justice, we offers useful insights into the underlying processes through which work can be improved through this interrelation. The findings also highlight the application of concepts such as relative deficiencies in the North Jakarta fire department to increase their level of work engagement.